BANK GUARANTEES - VASILE NEMES (Challenges of the Knowledge Society, 2012)
The present study propose the analyse of the irrevocable commitment of a bank entity towards a determined person, through which guarantees a certain legal conduct of its client, and, in case of breach, assumes the payment obligation of a determined amount of money. This kind of legal technique it is called bank guarantee and in the usual business language it is called “Letter of Bank Guarantee”. The determined reason to choose this scientific initiative it is the frequency of this kind of financial - banking commitments with various practical issues which are occurred by the use of those. From the legal point of view, the bank guarantees are not under an own legal regulation and are based on the common law, used in the guarantees domain. Through the new aspects of the actual Civil Code it are the legal regulation of the letter of bank guarantee and of the comfort letter, which shall constitute the main regulation in the negotiation and conclusion of a letter of bank guarantee or a bank comfort letter. For the legal reports with foreign elements, the parties can also use the Uniform Rules regarding the Guarantees at Request (URGR) Publish no.758/2010.